Identification and characterization of the vasa gene in the diamondback moth, Plutella xylostella. (July 2020) - Xu, Xuejiao; Yang, Jie; Harvey-Samuel, Tim; Huang, Yuping; Asad, Muhammad; Chen, Wei; He, Weiyi; Yang, Guang; Alphey, Luke; You, Minsheng
Abstract: Vasa is an ATP-dependent RNA helicase, participating in multiple biological processes. It has been widely used as a germ cell marker and its promoter has become a key component of several genetic pest control systems. Here we present the vasa gene structure and its promoter activity in Plutella xylostella, one of the most destructive pests of cruciferous crops. Full length Pxvasa cDNA sequences were obtained, revealing 14 exons and at least 30 alternatively spliced transcripts. Inferred amino acid sequences showed nine conserved DEAD-box family protein motifs with partial exclusion from some isoforms. Real-time quantitative PCR indicated the up-regulation of Pxvasa in both female and male adults compared with other developmental stages, and the expression levels of Pxvasa were found to be much higher in adult gonads, especially ovaries, than in other tissues. The putative promoter region of Pxvasa was sequenced and several ecdysone-induced transcription factor (TF) binding sites were predicted in silico . To further analyze the promoter region, two upstream regulatory fragments of different lengths were tested as putative promoters in transient cell and embryo expression assays, one of which was subsequently utilized to drive Cas9 expression in vivo . A transgenic line was recovered and the expression patterns of Cas9 and native Pxvasa were profiled in adult tissues and eggs with RT-PCR. This work provides the foundation for further studies on the gene functions of Pxvasa as well as the potential application of its promoter in genetic manipulation of P. xylostella . Graphical abstract: Image 1 Highlights: The  Plutella xylostella  homolog of vasa ( Pxvasa ) displays complex alternative-splicing isoforms. Pxvasa  showed a germline expression pattern but was also transcribed in somatic tissues. Pxvasa  promoters isolated in this work are able to drive transient expression of EGFP in insect cell lines and embryos. The  Pxvasa  promoter can drive Cas9 expression in DBM transgenics, which may be useful in binary CRISPR/Cas9 systems. This is the first report of constructing Vasa-driven Cas9 transgenic lines outside of the  Diptera .